Differential Benefits of Amoxicillin–Metronidazole in Different Phases of Periodontal Therapy in a Randomized Controlled Crossover Clinical Trial. Issue 3 (1st March 2015) - Mombelli, Andrea; Almaghlouth, Adnan; Cionca, Norbert; Courvoisier, Delphine S.; Giannopoulou, Catherine
Abstract : Background : The specific advantage of administering systemic antibiotics during initial, non‐surgical therapy or in the context of periodontal surgery is unclear. This study assesses the differential outcomes of periodontal therapy supplemented with amoxicillin–metronidazole during either the non‐surgical or the surgical treatment phase. Methods: This is a single‐center, randomized placebo‐controlled crossover clinical trial with a 1‐year follow‐up. Eighty participants with Aggregatibacter actinomycetemcomitans –associated moderate to advanced periodontitis were randomized into two treatment groups: group A, antibiotics (500 mg metronidazole plus 375 mg amoxicillin three times per day for 7 days) during the first, non‐surgical phase of periodontal therapy (T1) and placebo during the second, surgical phase (T2); and group B, placebo during T1 and antibiotics during T2. The number of sites with probing depth (PD) >4 mm and bleeding on probing (BOP) per patient was the primary outcome. Results: A total of 11, 212 sites were clinically monitored on 1, 870 teeth. T1 with antibiotics decreased the number of sites with PD >4 mm and BOP per patient significantly more than without (group A: from 34.5 to 5.7, 84%; group B: from 28.7 to 8.7, 70%; P <0.01). Twenty patients treated with antibiotics, but only eight treated with placebo, achieved a 10‐fold reduction of diseased sites ( P = 0.007). Consequently, fewer patients of group A needed additional therapy, the mean number of surgical interventions was lower, and treatment time in T2 was shorter. Six months after T2, the mean number of residual pockets (group A: 2.8 ± 5.2; group B: 2.2 ± 5.0) was not significantly different and was sustained over 12 months in both groups. Conclusion: Giving the antibiotics during T1 or T2 yielded similar long‐term outcomes, but antibiotics in T1 resolved the disease quicker and thus reduced the need for additional surgical intervention.